Peran Komunikasi Ayah dalam Perkembangan Mental Anak: Studi atas Santri Putri Pondok Tahfidz Karanganyar - Fitri Setianingsih (Academica: Journal of Multidisciplinary Studies, 2017)
This article attempts to explore the role of father’s communication in a child's mental development. Using a descriptive qualitative approach, the data were collected by interviewing 10 informants at Pondok Tahfidz Karanganyar, then the data were analyzed by literature review. The results showed that father's communication to children is very important in forming the child's mental. In addition, harsh communication to the children will negatively affect the child's mental development, so they become testy, often moody, and difficult to socialize. The quality of father and child communication is influenced by several factors, such as education level and family economic condition. Thus, the father must pay attention to the quality of his communication in order to form a positive mentality to the child.Keywords:father, communication, child’s mental development